The Location of Missense Variants in the Human GIP Gene Is Indicative for Natural Selection - Lindquist, Peter; Gasbjerg, Lærke Smidt; Mokrosinski, Jacek; Holst, Jens Juul; Hauser, Alexander Sebastian; Rosenkilde, Mette Marie (Frontiers in Endocrinology, 2022)
The hormone, glucose-dependent insulinotropic polypeptide (GIP), is involved in important physiological functions, including blood glucose homeostasis, bone formation, and fat metabolism. While mutations leading to physiological changes can be identified in large-scale sequencing, no systematic investigation of GIP missense variants has been performed. Here, we identified 168 naturally occurring missense variants in the human GIP gene from three independent cohorts comprising ~720,000 individuals. We scrutinized amino acid changing variants scattered across the pre-pro-GIP peptide using in silico effect predictions, which revealed that the sequence of the fully processed GIP hormone is more protected against mutations than the rest of the precursor protein. Thus, we observed a highly species-orthologous and population-specific conservation of the GIP peptide sequence, suggestive of evolutionary constraints to preserve the GIP peptide sequence. Elucidating the mutational landscape of GIP variants and how they affect the structural and functional architecture of GIP can aid future biological characterization and clinical translation.